Marketing Mix dan Kewirausahaan - Devi, Shinta Prasetia; Mahardhika, Early Harison; Rahayu, Wening Patmi; Winarno, Agung (FEB Universitas Maritim Semarang, 2025)
Entrepreneurship plays a crucial role in economic growth, especially for small and medium enterprises (SMEs). One of the main factors for entrepreneurial success is the effective implementation of the marketing mix. This paper discusses the concept of the marketing mix in entrepreneurship by highlighting the 4P elements (Product, Price, Place, Promotion) which have evolved into 7P with the addition of People, Process, and Physical Evidence. The discussion includes the implementation of the marketing mix, strategies for facing business challenges, and its impact on competitiveness and business growth. This study highlights how entrepreneurs can optimize marketing elements through product innovation, value-based pricing strategies, the use of digitalization in distribution, as well as social media-based promotion and marketing technology. Additionally, this paper reviews various challenges in the implementation of the marketing mix, such as limited capital, intense competition, and changes in consumer behavior, as well as adaptation strategies through guerrilla marketing, strategic partnerships, and data-driven approaches. The findings in this study indicate that the application of a flexible and innovative marketing mix can enhance business competitiveness and sustainability. By understanding the relationship between the marketing mix and entrepreneurship, entrepreneurs can develop more effective marketing strategies to face the ever-evolving market dynamics.